Quando o exame neurológico não tranquiliza: um caso de doença de Creutzfeldt-Jakob (Portuguese Journal of Family Medicine and General Practice, 2022)
Introduction: Creutzfeldt-Jakob Disease (CJD) is the most common human prion disease. Most cases are sporadic and occur as rapidly progressive dementia. In this case, the authors highlight the importance of the initial suspicion of a CJD, despite its rarity, in order to anticipate health and social needs.Case description: A 53-year-old woman went to her Family Health Unit for dizziness, imbalance, and dysthymic mood. A few days later, she presented with horizontal nystagmus, gait ataxia, and dysmetria of the upper limbs, for which she was referred to neurology for observation. In a few weeks, the clinical picture evolved into difficulty in performing activities of daily living, apathy, poor speech, memory difficulties, and dressing apraxia. Neurological examination revealed left hyperreflexia, left extension cutaneous-plantar reflex, a dystonic posture of both upper limbs, and spontaneous myoclonus, with a startle to sound stimulus. Magnetic resonance imaging (MRI) showed signals suggestive of CJD. Electroencephalography (EEG) and the 14-3-3 positive protein supported the diagnosis. Neurological status deteriorated rapidly, with progression to akinetic mutism, spastic tetraparesis, and death.Comment: CJD should be considered in the presence of rapidly progressive dementia and myoclonus. Cerebellar manifestations are initial symptoms in 20% to 40% of cases. Diffusion MRI, 14-3-3 protein detection, and EEG are useful for diagnosis. A definitive diagnosis requires a combination of neuropathological findings. Treatment is only supportive and the outcome is fatal, and it is crucial to show availability and support in medical, psychological, social, and family matters.
Keywords: Creutzfeldt-Jakob disease; Prion diseases; Dementia